Measuring and Analyzing the Effect of Innovation on Economic Growth: A Study of Selected Countries for the Period (2020-2022) - Sahho, Nazhan; Khudhair, Muneam; Abdullah, Gailan (Research Parks Publishers, 2024)
This research aims to study and analyze the impact of the Global Innovation Index (GII) 2020 on Gross Domestic Product (GDP) [as an indicator to express Economic Growth] for the year 2022 across a selected sample of countries worldwide using Eviews-13 software. The returns indicate that global innovation has a positive and significant effect on the GDP of the sample comprising 78 countries, categorized into three groups based on income: high-income countries, upper-middle-income countries, and lower-middle-income countries. This aligns with the research hypothesis. The impact varied according to the coefficient of determination (R²), explaining 61% of the changes in GDP due to variations in the GII for high-income countries, 44% for upper-middle-income countries, and 32% for lower-middle-income countries. The research also identified a long-term equilibrium relationship between the GII and GDP based on cointegration results. Additionally, there were no issues of autocorrelation or heteroscedasticity at a significance level of 5% for the model variables across all three groups in the sample. The research recommends several suggestions, the most important being the necessity for middle-income and low-income countries (developing nations) to enhance their innovation index in line with improving the components of this index to boost their GDP. Furthermore, developing countries need to rely on a knowledge-based economy grounded in creativity and innovation in the context of global competition, making human development vital for accommodating and advancing all technological innovations.